ENGLISH NEEDS ANALYSIS TO IMPROVE TECHNICAL COMPETENCE OF VOCATIONAL AUTOMOTIVE STUDENT - Maulana, Ridwan; Rahayu Nurjamin, Lucky; Dewi, Sinta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze English language skills in one of the schools in Garut Regency with a focus on automotive majors, in order to improve their technical competence. This study examines the English language skills needed in the automotive industry and evaluates the effectiveness of the current curriculum. Through qualitative methods, including interviews, this study found that although the curriculum partially meets the needs of the industry, there are gaps in students' English skills. The results showed that students face challenges in mastering technical vocabulary, manual reading comprehension, and effective communication in the automotive sector. In addition, the lack of industry-specific materials in the curriculum further complicates their learning process. Recommendations are provided to improve the alignment of the curriculum with industry needs through the integration of practical applications and improved teacher training.